A Bibliometric Analysis of Race-Related Research in LIS - Mongeon, Philippe; Brown, Alison; Dhaliwal, Ratna; Hill, Jessalyn; Matthews, Amber (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
<span data-sheets-value="{"1":2,"2":"The purpose of this work in progress is to quantify the amount of attention given to questions of racial inequity experienced by BIPOC in LIS research. We find that despite a recent surge in BIPOC-related research output, the publications are low in numbers and tend to receive fewer citations than other work in the same research area. BIPOC-related research is present but unevenly distributed across several areas of the field. These trends may help create and sustain momentum towards addressing the persistent lack of diversity and equity in LIS."}" data-sheets-userformat="{"2":8961,"3":{"1":0},"11":0,"12":0,"16":12}">The purpose of this work in progress is to quantify the amount of attention given to questions of racial inequity experienced by BIPOC in LIS research. We find that despite a recent surge in BIPOC-related research output, the publications are low in numbers and tend to receive fewer citations than other work in the same research area. BIPOC-related research is present but unevenly distributed across several areas of the field. These trends may help create and sustain momentum towards addressing the persistent lack of diversity and equity in LIS.